2018
DOI: 10.3329/jbau.v16i1.36497
|View full text |Cite
|
Sign up to set email alerts
|

Effects of soaking and grinding conditions on anti-nutrient and nutrient contents of soy milk

Abstract: Although soy milk is a very good source of nutrient with high biological value, the presence of anti-nutritional factors affects its nutrition quality and limits bioavailability of the nutrients. The effects of soaking duration and combination of soaking and grinding (hot or cold) on phytate, lipoxygenase, urease, trypsin inhibitor activity, protein solubility and other nutrient contents were investigated. Soaking alone at 55 and 60oC for different durations was found effective for the reduction of lipoxygense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…The blanched soybeans were ground with the addition of hot water (100°C) at a ratio of 4:1 (water: soybean) using a super mass colloider (Masuko Sangyo Co. Ltd., Kawaguchi, Japan) (Nowshin et al, 2018). Soy okara was collected after soy milk extraction using disk centrifuge and filtering through double layer cheese cloth.…”
Section: Preparation Of Soy Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…The blanched soybeans were ground with the addition of hot water (100°C) at a ratio of 4:1 (water: soybean) using a super mass colloider (Masuko Sangyo Co. Ltd., Kawaguchi, Japan) (Nowshin et al, 2018). Soy okara was collected after soy milk extraction using disk centrifuge and filtering through double layer cheese cloth.…”
Section: Preparation Of Soy Ofmentioning
confidence: 99%
“…Kamble et al (2019) found that reduced IVPD of okara-enriched pasta might be due to the presence of high levels of dietary trypsin inhibitors and other anti-nutrients in okara flour that reduced IVPD by inhibiting the action of proteolytic enzymes. However, heat treatment can reduce the anti-nutrient in soybean and soybean products and increase the protein digestibility (Nowshin et al, 2018).…”
mentioning
confidence: 99%
“…However, the FM content in the control diet was 45% while CBM was 0%. Soybean used for diet formulation was toasted (Ogunji, 2004), before grinding to lessen antinutritional factors (Iheanacho et al, 2019; Nowshin et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…The combination of soaking (60°C for 6 h), blanching (80°C for 10 min), and hot grinding (100°C) inactivated about 27% of phytate in soymilk. When soaking soybeans at 55°C or 60°C for 4 h under the same blanching and grinding conditions, greater levels of total solids (7.65-8.36%) and protein (4.46-5.67%) were yielded than those of cold grinding (6.37-6.55% for total solids and 4.02-4.13% for protein) (p < .05) (Nowshin et al, 2018). Soymilk from roasted soybeans at 110°C for 20-80 min and 120°C for 20 min retained a comparable protein content (3.1-3.6%) to raw soymilk (3.4%) (Navicha et al, 2017).…”
Section: Phytatementioning
confidence: 97%